2007
DOI: 10.1007/s00005-007-0014-x
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of the NADPH oxidase activity and anti-microbial function of neutrophils by arachidonic acid

Abstract: Arachidonic acid (AA), a second-messenger molecule released from membrane phospholipids by phospholipase A(2) in activated cells, is a stimulator of neutrophil responses, including the oxygen-dependent respiratory burst. The polyunsaturated fatty acid is also the precursor of biologically active eicosanoids. There are several mechanisms by which AA stimulates the respiratory burst. These include the direct binding of AA to S100 proteins which regulate the assembly of the NADPH oxidase as well as the activation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0
3

Year Published

2009
2009
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 113 publications
1
20
0
3
Order By: Relevance
“…Activated PKCa phosphorylates and activates cPLA 2 (19), resulting in the release of arachidonate, which suppresses CRIg expression (14). Our studies have demonstrated that arachidonate can also stimulate cPLA 2 activity (29), most likely owing to its ability to stimulate PKCa activation (16,18), giving rise to a regulatory signaling loop (30). TNF-a, produced in response to LPS, activates cPLA 2 (31), explaining the cytokine's ability to inhibit CRIg expression.…”
Section: Discussionmentioning
confidence: 87%
“…Activated PKCa phosphorylates and activates cPLA 2 (19), resulting in the release of arachidonate, which suppresses CRIg expression (14). Our studies have demonstrated that arachidonate can also stimulate cPLA 2 activity (29), most likely owing to its ability to stimulate PKCa activation (16,18), giving rise to a regulatory signaling loop (30). TNF-a, produced in response to LPS, activates cPLA 2 (31), explaining the cytokine's ability to inhibit CRIg expression.…”
Section: Discussionmentioning
confidence: 87%
“…apocynin revealed a potential value to limit peroxynitrite formation in inflammatory conditions in vivo [11]. Among others, in airways, there are some pivotal sources of superoxide radical -NADPH oxidase in inflammatory cells [41], inhibited by apocynin, mitochondrial sources [42,43] and arachidonic acid (AA) metabolism [44].…”
Section: Discussionmentioning
confidence: 99%
“…Particularly, NEM has been reported to generate ROS by activation of membrane-bound NADPH oxidase which is known to exist in HepG2 cells (Ehleben et al, 1997;Cool et al, 1998). Moreover, AA is well known to have an essential role in the activation of the NADPH oxidase (Curnutte, 1985;Block et al, 2006;Hii and Ferrante, 2007;Kim et al, 2008). Thus one can easily speculate that NEM may generate ROS through activation of NADPH oxidase induced by AA released by activation of iPLA 2 in HepG2 cells.…”
Section: Discussionmentioning
confidence: 99%